Mutu Limabelas Lot Benih Kedelai (Glycine max [L.] Merr) yang Disimpan Sampai Enam Bulan pada Suhu Ruang Berbeda - Agustiansyah, A; Nurmiaty, Yayuk; Ermawati, E; Putri, Anggita S. (Journal Galung Tropika, 2020)
The research aims to find the different quality of 15 lots of soybean seeds after storing until six months at room temperature (30 °C) and low temperature (±18°C). The study was conducted at the Seed and Plant Breeding Laboratory, Department of Agronomy and Horticulture, Faculty of Agriculture, the University of Lampung, from October 2017 to April 2018. This research was conducted in a Simple Randomized Design. Treatments were a combination of three soybean varieties, namely Anjasmoro, Grobogan, Burangrang, and five doses of SP-36 fertilizer, 0 kg/ha, 100 kg/ha, 150 kg/ha, 200 kg/ha, and 250 kg/ha. The results showed that soybean seed lots stored at low temperatures had high viability (>80%) after being held for six months compared to seeds stored at room temperature. Increasing the P fertilizer dose does not affect the quality of seeds stored at room temperature or low temperature.